Pengembangan Kemandirian Belajar Mahasiswa Melalui Presentasi Tugas dan Diskusi Pada Mata Kuliah Elektronika II - Erawan Kurniadi (Jurnal Pendidikan, 2011)
Learning Bology is focussed on the students’ involvement and activeness to make them easier to understand the instructional materials on the concepts of biology. To develop the existing teaching methodology at SMP Negeri I Karanganyar, Recoprocal Teaching is implemented as one of cooperative teaching strategy which enables the mutual activities of teachers and students under four understanding strategy, i.e. summerizing, questioning, clarifying and predicting. This research is intended to to identify the strategic significance of Reciprocal Teaching on the biology achievement of the seven graders of SMP Negeri 1 Karanganyar. The sample of this reserach are students of class VIIA and VIIB who are determined by random sampling technique. The t-test analysis technique results in computation that working t is 1.902 and table t is 1.675 under the level of sihnificance of 5%. The result shows that reciprocal Teaching has a significant influence on the achievement in biology of the students of VII graders of SMP Negeri 1 Karanganyar.